THE INFLUENCE OF WORK MOTIVATION, COOPERATION AND WORK CULTURE TOWARDS THE PERFOMANCE OF PT PLN (PERSERO) UP3 BEKASI EMPLOYEES - Tony Febriansyah; Kasmir Kasmir (Dinasti Publisher, 2022)
This research has purposes to reveal and investigate further the affects from work motivation, cooperation, and work culture towards the employee performance at PT PLN (Persero) UP3 Bekasi. The achievement of key performance indicator (KPI) distribution loss cannot be separated from work motivation from each employee. Good cooperation will provide maximum results in the implementation of work. In addition, with a well-developed work culture, every job could be sort out properly. The research method which applied was quantitative approach. The populations are 51 employees in the Energy Transaction Section and Network Section. The sampling technique used was saturated sampling with a total sample of 51 employees. Research data was collected through the distribution of questionnaires. Quantitative data analysis method through multiple linear regression method. The results indicates that 1) Work motivation partially has a strong and significant affect on employee performance. 2) Cooperation partially has a significant affect on employee performance. 3) Work culture Partially has a strong and significant affect on employee performance. 4) Work motivation, cooperation and work culture simultaneously have a positive and significant affect on employee performance. The research interpretation shows that the most powerful and significant factor in influencing the employee performance is the work motivation and followed by the cooperation and lastly the work culture variable.